Clinical relevance of interictal PET and interictal SPECT in localizing epileptogenic zones for surgical planning in mesial temporal sclerosis - Díaz-Peregrino, Roberto; San Juan Orta, Daniel; Alonso-Vanegas, Mario; Arellano-Reynoso, Alfonso; López-Hernández, David Omar; Morales-Morales, Miguel Angel; Camacho-Castillo, Evelin Zulema (Epilepsy & behavior, 2025)
Introduction - Accurate localization of the epileptogenic zone (EZ) is key to successful surgery in patients with mesial temporal sclerosis (MTS) and pharmacoresistant epilepsy. This study assesses the value of interictal PET and interictal SPECT in EZ identification and postsurgical outcomes. - Methods - A retrospective observational analysis was conducted on 60 patients who underwent SPECT and 49 who underwent PET, with results compared against VEEG and MRI findings. Key variables included seizure type, localization of EZ using SPECT with 99mTc-HMPAO and PET with [18F] FDG, and Engel classification at the latest follow-up. Kendall’s tau-c and Krippendorff’s alpha were used to assess agreement between imaging modalities. Logistic regression analysis was performed to identify variables associated with EZ localization and Engel I outcomes. - Results - PET identified the epileptogenic lesion in 87.8 % of cases, compared to 85 % for SPECT. PET showed a stronger correlation with VEEG and MRI (τb = 0.713 for both, p < 0.001) and greater concordance (α = 0.8171; 95 % CI 0.6762-0.9300) compared to SPECT (τb = 0.536 for both, p < 0.001 and α = 0.6999; 95 % CI 0.5360-0.8421). Adding one second to the ictal phase in VEEG increased the likelihood of detecting the EZ by 1.02 times using PET/SPECT (p = 0.009). Concordance between three neuroimaging modalities improved the probability of optimal surgical success (Engel I) by eight times (p = 0.041). - Conclusion - Interictal PET and interictal SPECT improve EZ localization in MTS patients, contributing to better surgical outcomes. PET showed slightly higher correlation and concordance with MRI and VEEG.